Anti-steatotic effects of an n-3 LCPUFA and extra virgin olive oil mixture in the liver of mice subjected to high-fat diet. Issue 1 (16th October 2015) - Valenzuela, Rodrigo; Espinosa, Alejandra; Llanos, Paola; Hernandez-Rodas, Maria Catalina; Barrera, Cynthia; Vergara, Daniela; Romero, Nalda; Pérez, Francisco; Ruz, Manuel; Videla, Luis A.
Abstract : We evaluated the anti-steatotic effects of n-3 long-chain polyunsaturated fatty acids plus extra virgin olive oil in the liver of mice fed a high fat diet. Abstract : Non-alcoholic fatty liver disease (NAFLD) is characterized by liver steatosis, oxidative stress, and drastic depletion of n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA), namely, eicosapentaenoic acid (C20:5 n-3, EPA) and docosahexaenoic acid (C22:6 n-3, DHA), which trigger lipolysis stimulation and lipogenesis inhibition. Extra virgin olive oil (EVOO) has important antioxidant effects. This study evaluated the anti-steatotic effects of n-3 LCPUFA plus EVOO in the liver of male C57BL/6J mice subjected to a control diet (CD) (10% fat, 20% protein, 70% carbohydrate) or high fat diet (HFD) (60% fat, 20% protein, 20% carbohydrate), without and with supplementation with n-3 LCPUFA (100 mg per kg per day) plus EVOO (100 mg per kg per day) for 12 weeks. HFD induced (i) liver steatosis (increased total fat, triacylglycerols, and free fatty acid total contents), (ii) higher fasting serum glucose and insulin levels and HOMA index, total cholesterol, triacylglycerols and TNF-α and IL-6, (iii) liver and plasma oxidative stress enhancement, (iv) depletion of the n-3 LCPUFA hepatic content, and (v) increment in lipogenic enzyme activity and reduction in lipolytic enzyme activity. These changes were either reduced ( p < 0.05) or normalized to control the values in animals subjected to HFD supplemented with n-3 LCPUFA plus EVOO. In conclusion, n-3 LCPUFA plus EVOO intervention exerts anti-steatotic effects underlying antioxidant and anti-inflammatory responses, improved insulin sensitivity, and recovery of the lipolytic/lipogenic status of the liver altered by HFD, and supports the potential therapeutic use of n-3 LCPUFA plus EVOO supplementation in the treatment of human liver steatosis induced by nutritional factors or other etiologies.